An unusual outbreak of rotavirus G8P[8] gastroenteritis in adults in an urban community, Singapore, 2016 - Chia, Gabriel; Ho, Hanley J.; Ng, Ching-Ging; Neo, Freddy Jun-Xian; Win, Mar-Kyaw; Cui, Lin; Leo, Yee-Sin; Chow, Angela (Journal of clinical virology, 2018)
•Rotavirus G8P[8] can cause gastroenteritis outbreaks in community-dwelling adults.•First rotavirus outbreak report in an adult urban community that is not waterborne.•Exposure to the market in the outbreak area was strongly associated with infection.•Transmission of rotavirus likely through fomites, person-to-person, and food-borne. An outbreak of gastroenteritis (GE) occurred in community-dwelling adults in the Central Region of urban Singapore, in May 2016. To investigate the cause of the outbreak. We conducted a case-cohort study on GE patients linked to the outbreak who presented to the emergency department of a tertiary-care hospital near the outbreak area, from 18 May to 11 June 2016. Stools were tested for gastrointestinal pathogens including rotavirus antigen and positive rotavirus samples were subject to genotyping. A total of 57 adult GE patients, with a median age of 40 (range 18 to 84) years, were included. Predominant symptoms were diarrhoea (98.2%), vomiting (64.9%), and abdominal discomfort (38.6%). Age 65 years and above (Adjusted OR 21.78, 95% CI 1.49–318.84; P = 0.02) was the only predictor of admission, after adjusting for comorbidities and clinical severity. Molecular microbiological investigations confirmed that the outbreak was caused by a novel human-bovine reassortant strain of rotavirus G8P[8] with DS-1-like backbone. Exposure to the market in the outbreak area was strongly associated with rotavirus infection (OR 46.14; 95% CI 43.04–49.25, P < 0.01). No particular food item could be identified as the outbreak cause. This is the first report of an outbreak of rotavirus G8P[8] in adults in an urban community that is not waterborne. Transmission was likely through fomites in the market and its surrounding areas, via consumption or contact with contaminated food items purchased from the market, and from person-to-person. The potential for novel G8P[8] strains to cause outbreaks cannot be overemphasized.